1998
DOI: 10.1099/00221287-144-1-45
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytochalasin A on apical growth, actin cytoskeleton organization and enzyme secretion in Aspergillus nidulans

Abstract: The role of actin in apical growth and enzyme secretion in the filamentous fungus Aspery(illuJ nidulans was studied by treating the hyphae with cytochalasin A (CA), which inhibits actin polymerization. Indirect immunofluorescence microscopy revealed actin at the tips of main hyphae and branches, and a t the sites of developing septa. CA inhibited the growth of the fungus and changed the growth pattern of hyphal tips from cylindrical tubes to spherical beads. The regions with swellings showed no actin fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 66 publications
11
112
0
1
Order By: Relevance
“…At the time of polarity establishment a few patches become associated with the germ tube emergence site ( Figure 1A). In germlings and mature hyphae, they are concentrated near the hyphal tip as was observed previously (Harris et al, 1994;Torralba et al, 1998), but we found that the pattern changes as the germlings grow into mature hyphae. In germlings, the patches are simply concentrated near (but not restricted to) the apex ( Figure 1B).…”
Section: Localization and Imaging Of Actin And Tropomyosin In Living supporting
confidence: 71%
See 4 more Smart Citations
“…At the time of polarity establishment a few patches become associated with the germ tube emergence site ( Figure 1A). In germlings and mature hyphae, they are concentrated near the hyphal tip as was observed previously (Harris et al, 1994;Torralba et al, 1998), but we found that the pattern changes as the germlings grow into mature hyphae. In germlings, the patches are simply concentrated near (but not restricted to) the apex ( Figure 1B).…”
Section: Localization and Imaging Of Actin And Tropomyosin In Living supporting
confidence: 71%
“…In previous studies, these have been difficult to image, but they have been visualized by immunofluorescence (Harris et al, 1994;Araujo-Bazán et al, 2008) and by using a GFP-tropomyosin fusion (Pearson et al, 2004). As reported previously (Harris et al, 1994;Torralba et al, 1998;Cheng et al, 2001), actin was also associated with forming septa (data not shown).…”
Section: Tip Growth Apparatus Of Aspergillusmentioning
confidence: 61%
See 3 more Smart Citations